ADULT EDUCATION IN UKRAINE: PRECONDITIONS OF FORMATION, PROSPECTS OF DEVELOPMENT - Лариса Лук'янова (Ivan Ziaziun Institute of Pedagogical Education and Adult Education of the NAES of Ukraine, 2020)
Socio-economic changes in the late 20th century and at the beginning of the 21st century, technological and socio-cultural transformations at global and local levels had a significant impact on de-termining the role of adult education for modern Ukrainian society and outline its further development vec-tor. The need for mass professional retraining of adults to ensure socio-economic reforms, as well as the for-mation of Ukraine's civil society, is prompted by the development of an adult continuous education flexible system to respond to the whole society's challenges and the demands of its specific layers. The author states that Ukraine has a rich historical experience of adult education (from weekend schools, re-education schools, part-time universities, universities for workers and peasants to the creation of research institutions in the system of the National Academy of Educational Sciences, engaged in research and theoretical analysis of an-dragogy and departments of andragogy at higher education institutions). Contemporary landscape of adult education in the country has been analyzed. According to the author, the situation is ambiguous and charac-terized by both positive (awareness of the role of adult education) and negative (reduction of terms of study, commercialization of many adult education pathways, funding cutbacks) features. However, positive changes prevail: branching of goals and education fields; diversification of educational services, development of adult education flexible structures that can meet modern requirements. The system of adult education in Ukraine has been analyzed. According to structural features, it has formal and informal components. The emphasis is placed on the role of non-formal education. The author concludes that adult education in Ukraine is gaining more importance in modern society.